IMPACT OF SYSTEMIC HEALTH ON IMPLANT SUCCESS - Dr Aditi Pustake, Dr. Anamika Shrikrishna Deshpande, Dr Sai Viswasri Immaneni, Dr Amna Bintul Huda, Dr Indu Thokala, Dr Krishna Sai Sushma Alahari (South Eastern European Journal of Public Health, 2025)
Dental implant therapy has revolutionized oral rehabilitation, offering predictable long-term success. However, systemic health plays a crucial role in implant survival, osseointegration, and overall treatment outcomes. Various systemic conditions, including diabetes mellitus, osteoporosis, cardiovascular diseases, and immunocompromised states, can negatively influence bone healing, peri-implant tissue health, and implant stability. Endocrine disorders, such as diabetes and thyroid dysfunction, alter bone metabolism and wound healing, potentially increasing the risk of implant failure. Similarly, medications like bisphosphonates and immunosuppressants affect osseointegration and bone remodeling. This review explores the complex interplay between systemic health and dental implant success, highlighting key pathophysiological mechanisms, clinical considerations, and strategies to optimize treatment outcomes in medically compromised patients. A thorough understanding of these factors enables clinicians to develop individualized treatment plans, ultimately improving implant longevity and patient satisfaction.